THE EFFECT OF JOB DESIGN AND COMPENSATION TOWARD EMPLOYEE SATISFACTION AT PT BNI TBK MANADO - Surina, Ni Wayan; Pangemanan, Sifrid S.; Tumiwa, Johan (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Abstract: The management of each company in the market today will definitely consider the satisfaction of employees, either for manufacturing or services .The process of preparing a variety of tasks and responsibilities for individuals to do their work and set design their work is very important: not only is the basis of individual satisfaction and achievement at work, but create work that is done in an efficient, economical, reliable and secure. The purpose of this research is to know the effect of job design and compensation toward employee satisfaction at PT BNI Manado simultaneously and partially. Find out the influence of Job Design and Compensation on the satisfaction of employee. This result employees regression analysis using primary data of 50 employees PT. BNI as the respondent of this research. The result of this research show that Job Design influence the Employee Satisfaction positively, significantly, and partially influence and that Compensation partially influence positively and significantly the Employee Satisfaction. It is shown also that above Job Design and Compensation simultaneously influence positively and significantly Employee Satisfaction. Keywords: job design, compensation, employee satisfaction